PENERAPAN MODEL INKUIRI MENGGUNAKAN MEDIA BAHAN ALAM UNTUK MENINGKATKAN HASIL BELAJAR SEL VOLTA - Maya Mutiasari (Universitas Terbuka, 2022)
This study aims to determine the improvement of student learning outcomes of class XII sciene semester 2 totaling 32 students by applying the Inquiry model to the voltaic cell material. The research method used is Classroom Action Research which consists of four stages, namely planning, action, observation, and reflection. This classroom action research was conducted in two cycles, the first cycle on the Cell Potential sub-concept, while the second cycle on the Voltaic Cell sub-concept. Data collection techniques were carried out by tests, observation sheets, and student response questionnaires to the learning process. The data analysis technique was qualitatively based on descriptive analysis of the results of the average calculation of the cognitive test results. Before the application of the inquiry model, the students' cognitive average value was 52.81 and after the application of the learning model with the inquiry model it became 67.41 with 44.00% classical completeness in the first cycle, then increased to 81,00 with 81,25% classical completeness in the second cycle. Most of the students' attitudes were positive towards learning with the Inquiry model and students were also more active in the learning process.